Overlap extension PCR cloning: a simple and reliable way to create recombinant plasmids - Anton V. Bryksin; Ichiro Matsumura (BioTechniques, 2010)
Here we describe a straightforward, efficient, and reliable way to clone an insert of choice into a plasmid of choice without restriction endonucleases or T4 DNA ligase. Chimeric primers containing plasmid sequence at the 5′ ends and insert sequence at the 3′ ends were used to PCR-amplify insertion sequences of various sizes, namely the genes for GFP (gfp), β-d-glucuronidase (gusA), and β-galactosidase (lacZ), as well as the entire luxABCDE operon. These inserts were employed as mega-primers in a second PCR with a circular plasmid template. The original plasmid templates were then destroyed in restriction digests with DpnI, and the overlap extension PCR products were used to transform competent Escherichia coli cells. Phusion DNA polymerase was used for the amplification and fusion reactions, so both reactions were easy to monitor and optimize.